1988
DOI: 10.1172/jci113323
|View full text |Cite
|
Sign up to set email alerts
|

Phagocyte-derived lactate stimulates oxygen consumption by Neisseria gonorrhoeae. An unrecognized aspect of the oxygen metabolism of phagocytosis.

Abstract: 02 consumption resulting from interaction of Neisseria gonorrhoeae and human neutrophils represents a composite of 02 consumed by the two cell systems. Experiments studying the relative contribution of each system suggested the possibility that gonococci increased their metabolic activity in response to interaction with neutrophils. This hypothesis was confirmed by demonstrating that undifferentiated HL-60 cells, which are unable to undergo a respiratory burst, induce a two-to threefold increase in gonococcal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
52
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 46 publications
9
52
0
Order By: Relevance
“…via inflammation (8)) and where pO 2 can be independently controlled. To meet these requirements, we devised a Matrigel® implant model that shows no ability by itself to induce neovascularization but supports new vessel growth when made host to an angiogenic signal (10).…”
Section: Lactate Deliverymentioning
confidence: 99%
“…via inflammation (8)) and where pO 2 can be independently controlled. To meet these requirements, we devised a Matrigel® implant model that shows no ability by itself to induce neovascularization but supports new vessel growth when made host to an angiogenic signal (10).…”
Section: Lactate Deliverymentioning
confidence: 99%
“…In support of the significance of nonoxidative killing, it has been shown that PMNs from people with chronic granulomatous disorder (NADPH oxidase deficient) had phagocytic killing capacities identical to PMNs from healthy donors (198) and that anaerobic PMNs kill as effectively as aerobic PMNs (46). N. gonor-rhoeae cells exposed to serum-or phagocyte-derived lactate have increased metabolism, including increased lactate dehydrogenase activity, and rapidly consume available molecular oxygen, reducing the ability of PMNs to mount an oxidative response (29)(30)(31)82). N. gonorrhoeae cells are also susceptible to the oxygen-independent components of PMN granules, including cathepsin G (45,197,(214)(215)(216)(217); reviewed in reference 218).…”
Section: Interactions Of N Gonorrhoeae With Host Cellsmentioning
confidence: 99%
“…However, the binding patterns are different between serum resistant and sensitive organisms (38 (49). Lactate is found in serum and is generated by phagocytes during aerobic glycolysis evoked by phagocytosis (50). The use of L(+)-lactate by gonococci is potentially important because of phenotypic changes that may occur through the use of this substrate (49), and because gonococci using L(+)-lactate demonstrate markedly accelerated competition for molecular oxygen (50).…”
mentioning
confidence: 99%
“…Lactate is found in serum and is generated by phagocytes during aerobic glycolysis evoked by phagocytosis (50). The use of L(+)-lactate by gonococci is potentially important because of phenotypic changes that may occur through the use of this substrate (49), and because gonococci using L(+)-lactate demonstrate markedly accelerated competition for molecular oxygen (50). Indeed, through competition for molecular oxygen gonococci may prevent neutrophil generation of oxidants (see below, and Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation